2‐Aminoethanol Extraction as a Method for Purifying Sc3N@C80 and for Differentiating Classes of Endohedral Fullerenes on the Basis of Reactivity. Issue 47 (6th October 2015) - Sarina, Evan A.; Mercado, Brandon Q.; Franco, Jimmy U.; Thompson, Christopher J.; Easterling, Michael L.; Olmstead, Marilyn M.; Balch, Alan L.
Abstract: Extraction with 2‐aminoethanol is an inexpensive method for removing empty cage fullerenes from the soluble extract from electric‐arc‐generated fullerene soot that contains endohedral metallofullerenes of the type Sc3 N@C2 n ( n =34, 39, 40). Our method of separation exploits the fact that C60, C70, and other larger, empty cage fullerenes are more susceptible to nucleophilic attack than endohedral fullerenes and that these adducts can be readily extracted into 2‐aminoethanol. This methodology has also been employed to examine the reactivity of the mixture of soluble endohedral fullerenes that result from doping graphite rods used in the Krätschmer–Huffman electric‐arc generator with the oxides of Y, Lu, Dy, Tb, and Gd. For example, with Y2 O3, we were able to detect by mass spectrometry several new families of endohedral fullerenes, namely Y3 C108 to Y3 C126, Y3 C107 to Y3 C125, Y4 C128 to Y4 C146, that resisted reactivity with 2‐aminoethanol more than the empty cage fullerenes and the mono‐ and dimetallo fullerenes. The discovery of the family Y3 C107 to Y3 C125 with odd numbers of carbon atoms is remarkable, since fullerene cages must involve even numbers of carbon atoms. The newly discovered families of endohedral fullerenes with the composition M4 C2 n (M=Y, Lu, Dy, Tb, and Gd) are unusually resistant to reaction with 2‐aminoethanol. Additionally, the individual endohedrals, Y3 C112 and M3 C102 (M=Lu, Dy, Tb and Gd), were remarkably less reactive toward 2‐aminoethanol. Abstract : Extraction with 2‐amino‐ethanol is a straightforward method for the isolation of Sc3 N@C80 from electric‐arc‐generated carbon soot and identification of new classes of unreactive endohedrals such a M3 C102 (see scheme).